Defluorination Effectiveness of Modified Biosand Filters - Okademi , Nancy; Odipo , Osano; Khazenzi , Judith (African Journal of Education,Science and Technology (AJEST), 2022)
The most substantial sources of fluoride exposure are located in the Rift valley. It has been reported that people in the Rift Valley are consuming water with up to 33 mg/L of fluoride. The WHO has set the maximum allowable limit for fluoride in potable water at 1.5 mg/L. For millions of Kenyans, drinking water with a high fluoride content is a health risk such as dental fluorosis and skeletal fluorosis. Several studies on deflouridation have been conducted, and the majority of them concentrate on separate treatments for flouride, even though mixed contamination is normal. Among Point of Use water treatment systems, the domestic biosand filter (BSF) is a low-cost technology that have been implemented in Kenya. Several studies have shown that the BSF can reduce the turbidity and microbial contaminants effectively however, limited studies have focused on removal of fluoride. Various low-cost materials like bamboo activated charcoal, bone char, diatomite and steel wool were investigated to assess their capacity to remove fluorides from water by batch adsorption studies. The measurements of the standard Biosand filter were scaled down and 18 modified filters were designed. The modified and standard Biosand filters were subjected to trials in the laboratory where 1.5, 2.26 and 3.0 mg/L initial fluoride concentration were subjected to 30-, 60- and 90-minutes contact time in order to reduce fluoride concentration to the desired level of below1.5 mg/L. Data obtained was subjected to microsoft Excel, t-test and analysis of variance (Anova). The modified filters absorbed a significant amount of fluoride (p>0.05). It was also observed that there was a significant removal on the contact time (p>0.05). Modified filter performed significantly better (p<0.05) than the standard filter, removing 97% of fluoride after 24 hours and treating the water to below the WHO fluoride limit of 1.5mg/L. Bamboo activated charcoal, diatomite, bone char and iron oxide (Fe0) removed 90, 85, 81 and 70% respectively. This study’s findings indicate that the modified filters can be effective in removing fluoride from water. The study recommends that ommunities impacted by elevated fluoride levels should adopt bone char modified biosand filters. Also, there should be a continuous evaluation of modified designs so that we can keep up with an upto date design that is efficient to its users.